Enterococcus faecium HDRsEf1 elevates the intestinal barrier defense against enterotoxigenic Escherichia coli and regulates occludin expression via activation of TLR‐2 and PI3K signalling pathways. (1st November 2018) - Yan, T.; Zhang, F.; He, Y.; Wang, X.; Jin, X.; Zhang, P.; Bi, D.
Abstract: Previously, we isolated a novel probiotic strain, designated HDRsEf1. In this study, we investigated the effects of this probiotic strain on intestinal barrier function and how it regulates the tight junction protein occludin in vitro . We used an ETEC‐infected mouse model for the in vivo experiment. Briefly, 40 ICR mice were randomly divided into four groups: control group, assigned to saline gavage; prevention group, given HDRsEf1 before and saline after infection with ETEC; infection group, given saline both before and after infection with ETEC; treatment group, given saline before and HDRsEf1 after infection with ETEC. The weight loss was alleviated both in the prevention and treatment groups. The ETEC‐induced intestinal inflammation was alleviated and the occludin mRNA expression levels in the jejuna of infected mice were increased in the prevention group. We explored the mechanism by which HDRsEf1 regulates occludin expression in vitro and found that HDRsEf1 prevented the downregulation of occludin expression in the prevention group. Simultaneously, we found that toll‐like receptor‐2 (TLR‐2) and phosphoinositide 3‐kinase (PI3K) play an important role in maintaining occludin expression. Therefore, we concluded that HDRsEf1 can prevent ETEC‐induced infection by enhancing the intestinal barrier function and increasing the expression levels of occludin. Significance and Impact of the Study: Enterotoxigenic Escherichia coli (ETEC) is a major cause of infectious diarrhoea in children, and porcine ETEC has been the leading cause of post‐weaning diarrhoea (PWD) in pigs. In our present study, we demonstrated for the first time that HDRsEf1 protects occludin from ETEC‐induced suppression. Moreover, HDRsEf1 was found to regulate occludin expression via TLR‐2 activation and the PI3K pathway. The results provide insights into the mechanism by which HDRsEf1 protects cells against ETEC infection and a rationale for the use of HDRsEf1 as a therapeutic and preventative agent.